2014
DOI: 10.1097/01.ogx.0000442817.34860.71
|View full text |Cite
|
Sign up to set email alerts
|

Telemedicine Collaboration Improves Perinatal Regionalization and Lowers Statewide Infant Mortality

Abstract: OBJECTIVES-We assessed a telemedicine (TM) network's effects on decreasing deliveries of very low birth-weight (VLBW, <1500 grams) neonates in hospitals without Neonatal Intensive Care Units (NICUs) and statewide infant mortality.STUDY DESIGN-This prospective study used obstetrical and neonatal interventions through TM consults, education, and census rounds with 9 hospitals from July 1, 2009 -March 31, 2010. Using a generalized linear model, Medicaid data compared VLBW birth sites, mortality, and morbidity bef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 25 publications
(34 reference statements)
0
11
0
Order By: Relevance
“…8 For hospitalized patients there are numerous reports of using telehealth for rapid evaluation for intensive care and subspecialty consults such as dermatology, infectious diseases, and psychiatry, where a thorough chart review, history, and visual exam may provide consultants with sufficient information to make clinical recommendations. [9][10][11][12][13][14][15][16][17][18] Telehealth has also been used to engage patients and families in their care during and after hospitalization. [19][20][21] One major limitation to the widespread adoption of telehealth initiatives has been the lack of payment models 22 however, in response to the COVID-19 pandemic both federal and state governments have loosened restrictions on privacy and billing for telehealth visits in an effort to allow health care providers to continue to care for patients while reducing potential exposure to the virus.…”
Section: Background and Significancementioning
confidence: 99%
“…8 For hospitalized patients there are numerous reports of using telehealth for rapid evaluation for intensive care and subspecialty consults such as dermatology, infectious diseases, and psychiatry, where a thorough chart review, history, and visual exam may provide consultants with sufficient information to make clinical recommendations. [9][10][11][12][13][14][15][16][17][18] Telehealth has also been used to engage patients and families in their care during and after hospitalization. [19][20][21] One major limitation to the widespread adoption of telehealth initiatives has been the lack of payment models 22 however, in response to the COVID-19 pandemic both federal and state governments have loosened restrictions on privacy and billing for telehealth visits in an effort to allow health care providers to continue to care for patients while reducing potential exposure to the virus.…”
Section: Background and Significancementioning
confidence: 99%
“…A study by Kim et al (2014) found positive impacts in delivery patterns in non-NICU hospitals using telemedicine services. 70 Ganesan et al presented a classic example of collaboration using ICTs in health sector to increase physical activity resulting in increased outcome. Academic researchers teamed up with the private sector professionals to implement and monitor the 100-day Stepathlon programme among 70,000 participants where most of the participants were from developing countries.…”
Section: Discussionmentioning
confidence: 99%
“…Telemedicine and tele-sonography have been used in states with large rural populations such as Arkansas. 28,29 This is a growing trend, both internationally and in the United States.…”
Section: Perinatal Regionalizationmentioning
confidence: 99%